Impact of Artificial Intelligence on Bangladesh Stock Market: Bibliometric Approach - Sharmin, Shadia; Joy, Md. Ashif Mahmud; Islam, A.T.M. Fahimul; Aubhi, Rezwan Ul Haque (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This research indicates that the hypothesis of artificial intelligence's effects on the stock market is fundamental to economics and has far-reaching implications for a variety of disciplines. This bibliometric analysis demonstrates the significance of this hypothesis, which should encourage academicians to engage in more inter-disciplinary research. The quantitative characteristics and significance of scholarly works from around the world were determined by employing a variety of analytical performance measures. The authors used VosViewer software to complete the Science Mapping section and found variety of results which shows the concepts’ vastness. Future researchers can anticipate further advancements in the field due to the positive trend in research and the enormous significance of the published works.